Turbulence and Unemployment in a Job Matching Model - Wouter J. den Haan; Christian Haefke; Garey Ramey (Institute for the Study of Labor (IZA), 2004)
According to Ljungqvist and Sargent (1998), high European unemployment since the 1980s can be explained by a rise in economic turbulence, leading to greater numbers of unemployed workers with obsolete skills. These workers refuse new jobs due to high unemployment benefits. In this paper we reassess the turbulence-unemployment relationship using a matching model with endogenous job destruction. In our model, higher turbulence reduces the incentives of employed workers to leave their jobs. If turbulence has only a tiny effect on the skills of workers experiencing endogenous separation, then the results of Ljungqvist and Sargent (1998, 2004) are reversed, and higher turbulence leads to a reduction in unemployment. Thus, changes in turbulence cannot provide an explanation for European unemployment that reconciles the incentives of both unemployed and employed workers.
Keywords: J64; E24; 330; skill loss; European unemployment puzzle; Arbeitslosigkeit; Qualifikation; Arbeitsmobilität; EU-Staaten